Stepwise Sous-Vide Cooking as a Novel Approach to Enhance the Water-Holding Capacity and Tenderness of Chicken Breast - Sin-Woo Noh; Dong-Heon Song; Hyun-Wook Kim (Foods)
Optimal sous-vide and multiphase cooking strategies remain underexplored despite their potential to improve the tenderness and juiciness of chicken breast. This study aimed to optimize sous-vide cooking conditions (Experiment I) and evaluate the effects of stepwise sous-vide cooking on the quality attributes (Experiment II). In Experiment I, a two-factor, three-level central composite design was employed to optimize the temperature (50, 60, and 70 °C) and time (3, 4.5, and 6 h) using response surface methodology. The optimal condition (55 °C for 3 h) significantly reduced cooking loss (11.47%) and shear force (11.84 N). In Experiment II, five cooking conditions were compared: conventional control (75 °C/30 min), sous-vide control (55 °C/180 min), and three stepwise methods (Stepwise I, 45 °C/180 min + 55 °C/180 min; Stepwise II, 55 °C/180 min + 75 °C/8.5 min; and Stepwise III, 55 °C/180 min + 95 °C/3 min). Stepwise II and III increased cooking loss (16.4% and 20.5%, respectively) and reduced moisture (p < 0.05), but Stepwise II significantly decreased shear force (12.50 N), retaining moisture comparable to conventional control (17.35 N). Stepwise sous-vide cooking, particularly Stepwise II, appears promising for enhancing tenderness without causing excessive water loss. Further research should evaluate the sensory properties and microbiological safety for potential practical applications.